Comparative religious ethics : a narrative approach to global ethics - Fasching, Darrell J., 1944-; deChant, Dell.; Lantigua, David M. (Chichester, West Sussex : Wiley-Blackwell, 2011)
'This popular textbook has been thoroughly revised and updated to reflect recent global developments, whilst retaining its unique and compelling narrative-style approach. Using ancient stories from diverse religions, it explores a broad range of important and complex moral issues, resulting in a truly reader-friendly and comparative introduction to religious ethics. A thoroughly revised and expanded new edition of this popular textbook, yet retains the unique narrative-style approach which has proved so successful with students Considers the ways in which ancient stories from diverse religions, such as the Bhagavad Gita and the lives of Jesus and Buddha, have provided ethical orientation in the modern world Updated to reflect recent discussions on globalization and its influence on cross-cultural and comparative ethics, economic dimensions to ethics, Gandhian traditions, and global ethics in an age of terrorism Expands coverage of Asian religions, quest narratives, the religious and philosophical approach to ethics in the West, and considers Chinese influences on Thich Nhat Hanh's Zen Buddhism, and Augustine's Confessions Accompanied by an instructor's manual which shows how to use the book in conjunction with contemporary films'--
'The new edition of this popular textbook has been thoroughly revised and updated to reflect recent global developments. The book retains the unique and compelling narrative-style approach which has proved so successful with students; reflecting the ways in which ancient stories from diverse religions, such as the Bhagavad Gita and the lives of Jesus and Buddha, have been used to project an ethical framework and provide ethical orientation in the modern world. New to this edition are discussions of globalization and its influence on cross-cultural and comparative ethics, economic dimensions to ethics, Gandhian traditions, and global ethics in an age of terrorism. The book also considers Chinese influences on Thich Nhat Hanh's Zen Buddhism, and Augustine's Confessions. Greater in-depth discussions are included on Asian religions, quest narratives, and the religious and philosophical approach to ethics in the West. Exploring a broad range of important and complex moral issues in a clear and absorbing style, this is a truly reader-friendly and comparative introduction to religious ethics'--
Includes bibliographical references and indexes.
Keywords: Religious ethics -- Comparative studies